2023
DOI: 10.1051/0004-6361/202244015
|View full text |Cite
|
Sign up to set email alerts
|

Type II radio bursts and their association with coronal mass ejections in solar cycles 23 and 24

Abstract: Context. Meter-wavelength type II solar radio bursts are thought to be the signatures of shock-accelerated electrons in the corona. Studying these bursts can give information about the initial kinematics, dynamics, and energetics of coronal mass ejections (CMEs) in the absence of white-light observations. Aims. We investigate the occurrence of type II bursts in solar cycles 23 and 24 and their association with CMEs. We also explore whether type II bursts might occur in the absence of a CME. Methods. We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 71 publications
2
3
0
Order By: Relevance
“…The exact distributions, also over the remaining SN configurations and the split into for m-II only and m+IP type II bursts, are shown in the Table 1. Kumari et al (2023) also investigated the correlation between number of SNs and type-II radio bursts and the reported correlations are consistent with our results.…”
Section: Type II Bursts and Sn Typessupporting
confidence: 86%
See 3 more Smart Citations
“…The exact distributions, also over the remaining SN configurations and the split into for m-II only and m+IP type II bursts, are shown in the Table 1. Kumari et al (2023) also investigated the correlation between number of SNs and type-II radio bursts and the reported correlations are consistent with our results.…”
Section: Type II Bursts and Sn Typessupporting
confidence: 86%
“…These findings are represented in Figures 7 and 8, respectively. The number of type II events associated with CMEs is 316/429 (74%), which is consistent with Kumari et al (2023) for SC 23 where they found 79% association, however, they report this association to be 95% in SC 24. In our list, among the 316 CME-associated type IIs, m-IIs are 54% (231/429 or 73% as a fraction of the entire CME smaple, 231/316), whereas the m+IP-II events are only 20% (85/429, or 27%, 85/316).…”
Section: Type II Bursts and Cmessupporting
confidence: 83%
See 2 more Smart Citations
“…During their eruptions, CMEs can travel at speeds ranging from several tens to even thousands of kilometers per second (Yashiro et al 2004;Webb & Howard 2012), potentially carrying mass from 10 13 to 10 16 g and releasing energy from 10 27 to 10 32 erg (Vourlidas et al 2000(Vourlidas et al , 2010. Their occurrence rates depend on the corresponding solar activity level (Yashiro et al 2008;Lamy et al 2019;Song et al 2021;Kumari et al 2023), which increases from roughly 0.5 day −1 during solar minimum to 6 day −1 during solar maximum (Gopalswamy et al 2003). CMEs originate primarily near the equatorial region during solar minimum, whereas they are ejected from all latitudes during solar maximum (Yashiro et al 2004).…”
Section: Introductionmentioning
confidence: 99%